2017
DOI: 10.15761/bgg.1000128
|View full text |Cite
|
Sign up to set email alerts
|

Detection and analysis of DNA material in human blastocoel fluid

Abstract: Preimplantation genetic diagnosis (PGD) is becoming a widely-accepted technique during in vitro fertilization (IVF). However, a disadvantage of PGD is the invasive biopsy methods used to sample embryonic cells or polar bodies. Recent studies have found that genetic material can be detected in blastocoel fluid (BF) and culture medium. In our study, BF and trophectoderm (TE) cells were simultaneously collected from the same donated human blastula. To generate enough DNA for analysis, we used multiple displacemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…also used similar methods, with an amplification success rate of 72.7% (8/11); the amplification efficiency of hotspot mutation regions of ten randomly selected genes was 84.0% (42/50). In spinal muscular atrophy and phenylpropionate ketoneuria, a total of seven samples had 100% WGA success rates, and the sequences of six BF samples were consistent with their paired TE results [33] . However, in a study by Capalbo et al [26] ,.…”
Section: Cfdna Research Based On Bfmentioning
confidence: 65%
“…also used similar methods, with an amplification success rate of 72.7% (8/11); the amplification efficiency of hotspot mutation regions of ten randomly selected genes was 84.0% (42/50). In spinal muscular atrophy and phenylpropionate ketoneuria, a total of seven samples had 100% WGA success rates, and the sequences of six BF samples were consistent with their paired TE results [33] . However, in a study by Capalbo et al [26] ,.…”
Section: Cfdna Research Based On Bfmentioning
confidence: 65%
“…The few available studies have assessed cfDNA on a very limited number of samples, either directly with the use of quantitative PCR (custom or validated TaqMan genotype assays) for the amplification of multicopy genes on chromosomes 17 and Y or the combined detection of specific gene variants and multiple SNPs surrounding them [ 61 , 82 ]. In other studies, whole genome amplification (PicoPlex or RepliG multiple displacement amplification, MDA) was followed by PCR for the amplification of specific regions of selected genes ( TCIRG1, SCN5A, RHO, EXTL1, SLC4A1, VWF, HSF4, NPC1, PTCH1, EPS8L3, SMN1, SRY, ACTB, PAH ) and validation of a couple of these by sequencing [ 58 , 82 , 83 ]. These studies, reviewed and summarized in a table in Leaver and Wells 2020, have demonstrated the possibility of cfDNA detection in BF but also underlined the limitations associated with variable and low detection rate, even after WGA, ranging from 42.9-84% (much lower in comparison to the ~95% efficiency WGA efficiency achieved from biopsied cells), increased allele dropout, risk of maternal contamination, lack of consistency and reliability [ 84 ].…”
Section: A Look Into the Strategies Employed For Nipgtmentioning
confidence: 99%
“…Whilst it could be argued that the relatively disappointing amplification rates in both studies could be associated with the use of the same WGA technology (PicoPLEX, Rubicon Genomics), PCR amplification rates were no better in a report following a multiple displacement amplification (MDA) based WGA approach (REPLI-g, Qiagen) applied to seven paired BF and trophectoderm biopsies (Shangguan et al, 2017). An attempt was made to amplify regions of the spinal muscular atrophy, phenylketonuria, SRY and ß-actin genes from WGA products.…”
Section: Pgt-m Using Blastocentesismentioning
confidence: 99%